EXTRACTION, PURIFICATION AND CHARACTERIZATION OF PROTEASE OF Pseudomonas fluorescens ISH AND IT’S ROLE IN DETERIORATION OF IRAQI SOFT CHEESE ISOLATION AND IDENTIFICATION OF Pseudomonas fluorescens AND DETERMINATION OF OPTIMUM CONDITIONS OF PROTEASE PRODUC - SEDRAH , ZIAD T.; A., AMER M.; AZIZ, GHAZI M. (Diyala Agricultural Sciences Journal, 2016)
The presence of psychrotrophic Pseudomonas fluorescens was investigated in samples of Iraqi soft cheese that produced in the dairy plant of the department of food science, college of Agriculture, University of Baghdad, Iraq. Depending on the cultural, morphological and biochemical tests and proteolysis, 24 isolates were diagnosed as proteolytic bacteria. The diagnosis was confirmed by Vitek 2 compact system. The most efficient 5 isolates were used to quantitative investigate protease production capability. The local isolate P. fluorescens ISH was the best in enzyme production (117.8 units/mg protein), and thus it was used in the current study to produce the enzyme by submerged cultures. The optimum conditions for protease production were the use of minimal salts medium with 1% skim milk and pH 8 at a 15OC for 96 hours and the inoculum size was 1 x 107 using shaking incubator at 125rpm of speed.